Spirituality and Religion in Higher Education - Gillespie, Catherine (Unfolding: University Chaplaincy in Practice, 2026)
This literature review synthesizes current empirical evidence on spirituality and religion in higher education to inform institutional practice and policy. First, religion and spirituality are defined. Second, the benefits of spirituality and religion among students in higher education are outlined and the struggles are highlighted. Third, how spirituality and religion are conceptually understood and assessed within a higher education environment is explored. Lastly, applications are presented, accompanied by recommendations for institutions.